2016
DOI: 10.1021/acs.oprd.5b00418
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Homogeneous Pd Catalyst Separation by Ceramic Membranes. Application to Downstream and Continuous Flow Processes

Abstract: Successful chemical production of molecules whilst simultaneously reducing the environmental impact of the process relies not only on more efficient reactions but also on developments in reactor and separation technology. Recent decades have also witnessed a significant growth in industrial interest in solvent based separations using membranes stable to organic solvents. The incorporation of membranes in to a chemical process can be via a simple downstream processing method or an integrated reaction membrane m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…An alternative approach to catalyst separation using membranes was undertaken by Ormerod and co-workers on IPr and related ligands. While early studies were carried out on IPr ligand [69], modification of the latter by appending long chains at the para-position of the phenyl ring (Figure 2, right) proved judicious for catalyst recovery through nanofiltration. This allowed the cross-coupling reaction in a semicontinuous mode in a membrane-assisted reactor [70].…”
Section: Entrymentioning
confidence: 99%
“…An alternative approach to catalyst separation using membranes was undertaken by Ormerod and co-workers on IPr and related ligands. While early studies were carried out on IPr ligand [69], modification of the latter by appending long chains at the para-position of the phenyl ring (Figure 2, right) proved judicious for catalyst recovery through nanofiltration. This allowed the cross-coupling reaction in a semicontinuous mode in a membrane-assisted reactor [70].…”
Section: Entrymentioning
confidence: 99%
“…The authors have reported the detection of little leaching (<1 ppm). Application to continuous flow process on a large scale was reported recently and could open new way for industrial use [95,96].…”
Section: Heterogeneous Suzuki-miyaura Cross-coupling Reaction In Contmentioning
confidence: 99%
“…Among numerous advantages the most attractive ones are facile automation, reproducibility, safety and process reliability due to constant reaction parameters (efficient mixing, temperature, time, amount of reagents, and solvent) [27]. Since flow reactors operate in a continuous mode, they can be conveniently coupled with further unit operations such as membrane separations [28][29].…”
Section: Process Configurationsmentioning
confidence: 99%
“…of continuous flow coil reactors with membrane separation can also be found in the literature. Ormerod et al developed a membrane process for the separation of NHC complexes of palladium catalysts from reaction mixtures using highly stable ceramic membranes [29]. Titanium dioxide based membranes with MWCO in the range of 450-1500 were screened.…”
Section: Palladium Catalysed Reactionsmentioning
confidence: 99%